Pengembangan Sistem Informasi Electronic Supply Chain Management (Studi Kasus: CV. Baiducha Technology) - Priambodo Aji Saputro; Himawat Aryadita; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
CV. Baiducha Technology is one of the manufacturing companies engaged in game equipment construction. Along with the development of the company towards a larger and complex, the existing information management system in the company became one of the obstacle fluency the internal production activities. So far, the company does not have an integrated system in processing all business activities, recording and processing of information flows of companies that are prone to error because it is still done manually, and also has not been integrated between the company and the supplier causing the company still make the process of ordering raw materials only through the telephone network. In addition, the absence of an information system that can manage the supply chain process in internal company more effectively and efficiently. This study aims to develop an Electronic Supply Chain Management information system that can assist in improving the company's performance in order to achieve efficiency and effectiveness in its business processes. Software development is done using a waterfall model, where there are several steps that must be done sequentially. On testing software functionality using blackbox method and whitebox method. Based on the results of functionality testing that has been done indicate that this system has met the needs in accordance with the specified specifications, and also the results of compatibility testing shows that the system can run well on various different browsers.